Laryngotracheal anomalies and airway fluoroscopy in infants. (June 2017) - Isaiah, Amal; Pereira, Kevin D.
Abstract: Objectives: The role of airway fluoroscopy in the diagnosis of laryngotracheal anomalies in infants is controversial. We aimed to (i) compare airway fluoroscopic characteristics with endoscopic findings in infants presenting for evaluation of upper airway obstruction and (ii) assess the as low as is reasonably achievable (ALARA) status for airway fluoroscopy as an initial diagnostic test in suspected laryngotracheal anomalies. Materials and methods: We performed a retrospective review of children who underwent fluoroscopy and endoscopic evaluation of the airway in the operating room for suspected laryngotracheal anatomic abnormalities. Thirty-four infants who underwent both procedures at at ertiary level university-based children's hospital from January 1, 2008 to December 1, 2013 were included. Infants with suspected foreign bodies or an existing tracheostomy were excluded. Intraoperative findings from endoscopy and radiologic interpretation from fluoroscopy were compared using standard tools for validation of a diagnostic test. These metrics were compared with historic data that suggested good correlation between radiologic and endoscopic findings in older children. Results: The median age was 3.6 months (range 1–8 months). The sensitivity of airway fluoroscopy for determining laryngotracheal pathology was 18%. Specificity, positive predictive value and negative predictive value were 83%, 67% and 35%, respectively. Although each fluoroscopic exposure was optimized for pediatric patients, the median cumulative exposure to ionizing radiation was 19 mR (range 10–34 mR). Conclusions: Airway fluoroscopy yields metrics that are overall poor to be considered a valid and accurate universal radiologic diagnostic test in infants evaluated for laryngotracheal pathology. The cumulative exposure to ionizing radiation from use of a fluoroscope cannot be justified by the sensitivity of the test and may not conform to ALARA standards for imaging in this population.